Cat scratch disease - a case report - Dr. Sujata S. Giriyan; Dr. Rajesh H. Chandan; Dr.Vasantham vyshnavi (Tropical Journal of Pathology and Microbiology, 2018)
Cat scratch disease is benign self-limiting infectious disease caused by B.Henselae. It can occur world-wide with no racial or sex predilection. Cats are the major reservoirs. Transmission can occur through biting, scratching and licking. Patients present with regional lymphadenopathy. A 17-year-old male presented with a single swelling in the inguinal region of 15 days duration. It was gradually increasing in size. The swelling measured 6cm * 5cm, soft to firm in consistency, non-tender. The mobility was restricted. Fine needle aspiration cytology was performed which was diagnosed as granulomatous lymphadenitis. The swelling was excised and sent for histopathological examination. Histopathologically, a final diagnosis of Cat-scratch lymphadenitis was made. Cat-scratch Disease is a self-limiting illness in an immuno-competent host. The associated lymphadenitis is mainly solitary and unilateral. Although it is not a unique diagnosis, Cat-scratch disease is required to implement appropriate and targeted antibiotic therapy.